Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
(3x + 2)(-x^3 - 3) =
3x(-x^3 - 3) + 2(-x^3 - 3) =
-3x^4 - 2x^3 - 9x - 6 <== result of multiplying (3x+2)(-x^3-3)
now multiply that by (3+x)...
(3+x)(-3x^4 - 2x^3 - 9x - 6) =
3(-3x^4 - 2x^3 - 9x - 6) + x(-3x^4 - 2x^3 - 9x - 6) =
-9x^4 -6x^3 - 27x - 18 - 3x^5 - 2x^4 - 9x^2 - 6x =
-3x^5 - 11x^4 - 6x^3 - 9x^2 - 33x - 18 <== result of multiplying by (3 + x)
the coefficient of x^4 = -11 <==
Step-by-step explanation:
Answer:
(3x + 2)(-x^3 - 3) =
3x(-x^3 - 3) + 2(-x^3 - 3) =
-3x^4 - 2x^3 - 9x - 6 <== result of multiplying (3x+2)(-x^3-3)
now multiply that by (3+x)...
(3+x)(-3x^4 - 2x^3 - 9x - 6) =
3(-3x^4 - 2x^3 - 9x - 6) + x(-3x^4 - 2x^3 - 9x - 6) =
-9x^4 -6x^3 - 27x - 18 - 3x^5 - 2x^4 - 9x^2 - 6x =
-3x^5 - 11x^4 - 6x^3 - 9x^2 - 33x - 18 <== result of multiplying by (3 + x)
the coefficient of x^4 = -11 <==
Step-by-step explanation:
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.